2016
DOI: 10.35426/iav45n118.02
|View full text |Cite
|
Sign up to set email alerts
|

El Valor Percibido del Destino Turístico en Relación con el Perfil del Turista en Acapulco, Guerrero-México

Abstract: Se analiza el valor percibido como un constructo multidimensional, que involucra otras dimensiones que generan beneficios positivos de valor en el consumidor turístico y no sólo la utilidad económica. El objetivo es relacionar el perfil del turista nacional durante su experiencia en el destino turístico, con el valor percibido de sus atributos. El método cuantitativo utiliza la encuesta a turistas, con análisis factorial y ANOVA se contrasta la hipótesis. Los resultados permiten considerar aspectos relacionado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
7
0
3
Order By: Relevance
“…Finally, his emotional value was also very similar to our emotional value. In the same perspective, Bags (2015) and Solís-Radilla et al (2016) found function-al, affective, and social values, which are similar to our economic-functional, emotional, and social values, respectively. Conversely, Kim and Thapa (2018) discovered quality, emotional, price, and social dimensions as perceived values, being closely related to the economic-functional, emotional, and social values, respectively, that emerged from this research.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Finally, his emotional value was also very similar to our emotional value. In the same perspective, Bags (2015) and Solís-Radilla et al (2016) found function-al, affective, and social values, which are similar to our economic-functional, emotional, and social values, respectively. Conversely, Kim and Thapa (2018) discovered quality, emotional, price, and social dimensions as perceived values, being closely related to the economic-functional, emotional, and social values, respectively, that emerged from this research.…”
Section: Discussionsupporting
confidence: 52%
“…Among the theoretical implications, previous literature has found four perceived values in ecotour-ism: economic, functional, emotional and social (Carvache Franco et al, 2019;Kim & Thapa, 2018;Park, 2017, Lee et al, 2007;Lee et al, 2010, Solís-Radilla et al, 2016Williams & Soutar, 2009). But as seen in this research, the economic and functional value can be merged into a single dimension called "economic and functional" value.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As previously mentioned, the perceived value involves the functional, affective and social dimensions, from which the general evaluation of the experience lived by the tourists is derived, and which, in turn, consists of the perception of the balance between the benefits obtained and the costs assumed (Bajs, 2015;Solís-Radilla et al, 2016;Zeithaml, 1988). Resulting from this interaction are the main components that contribute to the attitudes and behaviors of tourists towards the product or service (Rasoolimanesh et al, 2016).…”
Section: Sociodemographic Profile Of the Tourist Visiting Protected Nmentioning
confidence: 99%
“…Uno de los hallazgos indica que el factor del personal representa la dimensión más relevante para los turistas. Limitaciones del estudio como ser de corte transversal y la no aleatoriedad de la muestra impiden la generalización de los resultados (Solís et al, 2016).…”
unclassified